PERSEPSI MAHASISWA TERHADAP MATERI AJAR PADA PEMBELAJARAN ONLINE - Adijaya, Nuryansyah; Pertiwi, Ratih (Eduscience : Jurnal Ilmu Pendidikan, 2017)
Abstract Online learning is assumed as a new paradigm in learning-teaching process in which lecturer and students do not need to sit in the same room to make class activities. They just need a gadget with internet connection to create the activities. Along with the practical of online learning, many institutions or universities in Indonesia create online learning to support learning-teaching process. However, online learning still faces some problems in learning activity, one of the problems is the use of learning materials. This study is aimed to explore studentsâ perceptions toward the use of learning materials in online learning whether the learning materials already support their activity in online class. 100 students of online learning TOEFL 2 are targeted to be research data. They are given some questions to explore their perceptions related to their perceptions toward the use of learning material. Besides, some students are also interviewed to explore deeper information. Quantitative analysis is employed in the study. This study reveals that students cannot decide whether learning material used in online learning already support online class or not which shown by mean score that reaches 2, 805. they think materials are practical. However, they sometimes face some difficulties of using the materials; to understand instruction, responses, etc. These factors make students cannot decide their perception toward the use of learning material in online learning. That is why to support online learning, we must periodically revise learning materials for online learning. Â Keywords: online learning, studentsâ perception, learning materialÂ AbstrakPembelajaran online diasumsikan sebagai sebuah paradikma baru dalam proses pelajar mengajar dimana Dosen dan mahasiswa tidak perlu duduk di ruang yang sama untuk membuat akivitas kelas. Mereka hanya perlu gadget dengan koneksi internet untuk membuat aktivitas tersebut. Sejalan dengan kepraktisan dalam pembelajaran online, banyak institusi atau universitas di Indonesia menciptakan pembelajaran online untuk mendukung proses belajar mengajar. Namun, pembelajaran online masih mengalami kendala dalam aktivitasnya, salah satu masalah yang dihadapi adalah penggunaan materi ajar. Penelitian ini bertujuan untuk mengeksplorasi persepsi mahaiswa terhadap penggunaan materi ajar apakah materi pembelajaran yang digunakan sudah mendukung aktivitas dalam pembelajaran online. 100 mahasiswa mata kuliah TOEFL online dijadikan sasaran sebagai data penelitian. Mereka diberikan beberapa pertanyaan untuk menggali persepsi mereka terhadap penggunaan materi ajar. Selain itu beberapa mahasiswa juga diinterview untuk mendapakan informasi yang lebih mendalam. Analisis kuantitatif digunakan dalam penelitian ini. Penelitian ini mengungkapkan bahwa persepsi mahasiswa menunjukan netral atau tidak atau tidak dapat memutuskan apakah materi ajar yang digunakan sudah mendukung mereka dengan ditunjukan dengan skor rata-rata 2.805. Mereka mengungkapkan materi yang digunakan praktis, karena dapat dibuka dimana-mana, namun kadang ulit memahami materi, instruksi, dan sebagainya. Mungkin faktor-faktor ini yang membuat mereka tidak bersifat netral. Oleh karena itu untuk mendukung perkuliahan online, kita perlu melakukan perbaikan secara berkala.Â Kata kunci: pembelajaran online, materi ajar, persepsi mahasiswa